New admission scoring criteria for patients with odontogenic infections: a pilot study. Issue 1 (January 2017) - Sainuddin, Sajid; Hague, Richard; Howson, Kate; Clark, Stuart
Abstract: Odontogenic infections are often referred to the oral and maxillofacial surgical department, which can cause a dilemma for junior clinicians who have to decide whether such patients require admission. We have devised a score to be used on admission to our unit to help junior on-call staff, and designed a prospective pilot study to assess it.